2019
DOI: 10.5194/acp-19-14477-2019
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of synoptic circulation patterns on ozone variability in northern China from April to October 2013–2017

Abstract: Abstract. The characteristics of ozone variations and the impacts of synoptic and local meteorological factors in northern China were quantitatively analyzed during the warm season from 2013 to 2017 based on multi-city in situ ozone and meteorological data as well as meteorological reanalysis. The domain-averaged maximum daily 8 h running average O3 (MDA8 O3) concentration was 122±11 µg m−3, with an increase rate of 7.88 µg m−3 yr−1, and the three most polluted months were closely related to the variations in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 47 publications
3
65
1
Order By: Relevance
“…In addition, the SWP change includes both frequency and intensity changes. We find that the frequency change in SWPs has less impact on the inter-annual variation in O3 levels than the intensity change in SWPs, which is consistent with the results of Hegarty et al (2007) and Liu et al (2019). The contribution of intensity change and frequency change will be further discussed in section 3.4.…”
Section: Impacts Of Swp Change On O3 Concentration Variationsupporting
confidence: 87%
See 3 more Smart Citations
“…In addition, the SWP change includes both frequency and intensity changes. We find that the frequency change in SWPs has less impact on the inter-annual variation in O3 levels than the intensity change in SWPs, which is consistent with the results of Hegarty et al (2007) and Liu et al (2019). The contribution of intensity change and frequency change will be further discussed in section 3.4.…”
Section: Impacts Of Swp Change On O3 Concentration Variationsupporting
confidence: 87%
“…We further reconstructed the EOF1 time series by considering different SWPIIs due to the unique characteristics of each SWP. The results are better than those in Hegarty et al (2007) and Liu et al (2019) who used the same SWPIIs in all SWPs.…”
Section: Conclusion and Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The precursors of O3 included NOx and VOCs, but there was also a notable rise in O3, as NO2 decreased in 2014-2016. Considering the nonlinear relationship between O3 and its precursors, the decrease of NO2 in high NOx/VOC ratio conditions promoted O3 formation [37]. In addition, it was found that the large reduction of aerosol loading enhanced O3 production rate to stronger photolysis [38].…”
Section: The Implication Of Changing Air Pollution In Central Chinamentioning
confidence: 98%